기본간호학회지 게재 논문의 통계학적 방법 유형과 오류...Type of Statistical Methods and Errors in the Journal of Korean Academy of Fundamentals of Nursing - 최은희 (Journal of Korean Academy of Fundamentals of Nursing, 2015)
Purpose: In nursing research, studies using statistical methods are required and have increased. In this study, some statistical methods using in nursing study are summarized and appropriate usage is proposed. Methods: Twenty-five original articles from the Journal of Korean Academy of Fundamentals Nursing were reviewed. Statistical methods used in the Journal of Fundamentals Nursing were classified and common errors were presented. Results: Seventy-six statistical analysis were performed in the 25 studies. Among the articles, 28 cases contained errors. Most errors occurred in linear regression analysis and nonparametric analysis. Conclusion: When the use of statistical method is applied inappropriately, the result bring out a serious error. In order to ensure reliability and validity of study, researchers should recognize clear application and usage of statistical methods.